HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP DENGAN PERILAKU MENGHADAPI MENOPAUSE PADA IBU PREMENOPAUSE DI POSYANDU LANSIA KRAPYAK KOTA SEMARANG - Mularsih, Sri; Christianti, Yenny (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
This study aims to determine the relationship between knowledge and attitudes and behavior in facing menopause in premenopausal mothers at the Krapyak Elderly Posyandu, Semarang City. This type of research is correlation study research with quantitative methods. This research design uses a cross-sectional approach. The population was all premenopausal mothers at the Krapyak Elderly Posyandu, totaling 85 people. The sample was 70 respondents using purposive sampling technique. The research results showed that the majority were 47 years old, 27 respondents (38.6%); most had a high school education, 39 respondents (55.7%); mostly private, 26 respondents (37.1%); most of the knowledge was lacking as many as 29 respondents (41.4%); most of the attitudes were not good as many as 31 respondents (44.3%); most of the behavior is lacking as many as 37 respondents (52.9%); there is a relationship between knowledge and behavior in facing menopause in premenopausal mothers at Posyandu for the Elderly Krapyak Semarang because the p value (0.000) is smaller than 0.05; There is a relationship between attitudes and behavior in facing menopause in premenopausal mothers at Posyandu for the Elderly Krapyak Semarang because the p value (0.024) is smaller than 0.05.